JURIDIC ANALYSIS OF INDEPENDENT COMPANY ESTABLISHMENT POST GOVERNMENT REGULATION NUMBER 8 YEAR 2021 - Elvira Fitriani Pakpahan; Tommy Leonard; Syahruddin Nasution (Magister Kenotariatan Universitas Pasundan, 2021)
Abstract An individual company is a business entity that is a legal entity and is independently providing a glimmer of hope for the community in the form of convenience in the establishment, change, revocation of the company, and the legality of an individual company. In article 1 number 1 of Government Regulation Number 8 of 2021 it is stated that individual legal entities meet the criteria for micro and small businesses as stipulated in article 2 paragraph 1 letter b that the establishment of an individual company can be established by 1 (one) person by taking legal action in the form of making an electronic statement of the establishment to the minister, research problems on how to change the company, dissolution of an individual company after Government Regulation Number 8 of 2021, what is the legality and position of a sole proprietorship after Government Regulation Number 8 of 2021.